Biosafety and immunology: An interdisciplinary field for health priority - Jun Liu; Gary Wong; Hui Li; Yan Yang; Yuxi Cao; Yongfeng Li; Yan Wu; Zijie Zhang; Cong Jin; Xi Wang; Yongwen Chen; Bin Su; et al. (Elsevier, 2024)
Biosafety hazards can trigger a host immune response after infection, invasion, or contact with the host. Whether infection with a microorganism results in disease or biosafety concerns depends to a large extent on the immune status of the population. Therefore, it is essential to investigate the immunological characteristics of the host and the mechanisms of biological threats and agents to protect the host more effectively. Emerging and re-emerging infectious diseases, such as the current coronavirus disease 2019 (COVID-19) pandemic, have raised concerns regarding both biosafety and immunology worldwide. Interdisciplinary studies involved in biosafety and immunology are relevant in many fields, including the development of vaccines and other immune interventions such as monoclonal antibodies and T-cells, herd immunity (or population-level barrier immunity), immunopathology, and multispecies immunity, i.e., animals and even plants. Meanwhile, advances in immunological science and technology are occurring rapidly, resulting in important research achievements that may contribute to the recognition of emerging biosafety hazards, as well as early warning, prevention, and defense systems. This review provides an overview of the interdisciplinary field of biosafety and immunology. Close collaboration and innovative application of immunology in the field of biosafety is becoming essential for human health.